Zoonotic Tuberculosis – The Changing Landscape - Kock, Richard; Michel, Anita L.; Yeboah-Manu, Dorothy; Azhar, Esam I.; Torrelles, Jordi B.; Cadmus, Simeon I.; Brunton, Lucy; Chakaya, Jeremiah M.; Marais, Ben; Mboera, Leonard; Rahim, Zeaur; Haider, Najmul; et al. (International journal of infectious diseases, 2021)
•Globally, Zoonotic TB remains a poorly monitored and an important unaddressed burden.•Zoonotic TB primarily from consumption M. bovis contaminated unpasteurized dairy products.•Novel zoonotic TB strains (e.g. M. orygis), warrants more attention and intervention.•Early detection and control of M. bovis in cattle remains the mainstay of reducing zoonotic TB risk.•Reverse zoonosis to animals of treatment resistant TB strains is a threat to eliminating TB. Despite slow reductions in the annual burden of active human tuberculosis (TB) cases, zoonotic TB (zTB) remains a poorly monitored and an important unaddressed global problem. There is a higher incidence in some regions and countries, especially where close association exists between growing numbers of cattle (the major source of Mycobacterium bovis) and people, many suffering from poverty, and where dairy products are consumed unpasteurised. More attention needs to be focused on possible increased zTB incidence resulting from growth in dairy production globally and increased demand in low income countries in particular. Evidence of new zoonotic mycobacterial strains in South Asia and Africa (e.g. M. orygis), warrants urgent assessment of prevalence, potential drivers and risk in order to develop appropriate interventions. Control of M. bovis infection in cattle through detect and cull policies remain the mainstay of reducing zTB risk, whilst in certain circumstances animal vaccination is proving beneficial. New point of care diagnostics will help to detect animal infections and human cases. Given the high burden of human tuberculosis (caused by M. tuberculosis) in endemic areas, animals are affected by reverse zoonosis, including multi-drug resistant strains. This, may create drug resistant reservoirs of infection in animals. Like COVID-19, zTB is evolving in an ever-changing global landscape.